Mendidik Anak Autism Spectrum Disorder (ASD) di Kelas Reguler: Tantangan dan Kendala Guru (Jurnal Ilmiah Psikologi MIND SET, 2021)
The success achieved by ASD children in the learning process is determined by the way the teacher approves his role. This study discusses the role of teachers in the learning process of ASD children conducted in regular classes. This study uses a qualitative approach with data collection using structured interviews. The subjects of this study were 3 teachers who had different experiences in teaching ASD children. The results of this study show that in dealing with ASD children according to their needs, teachers who already know the basics of ASD children are needed, teachers who have extra patience, and teachers who have a strong mentality and teachers who have a very sincere conscience.